SPORTS INJURY AND REHABILITATION OF LOWER LIMB SOFT TISSUE - Zhu,Zhilin (2021)
ABSTRACT Introduction: the assessment and proper management of lower extremity soft tissue injury is very important. Because the mechanism and clinical manifestations of lower extremity soft tissue injury are varied, it is necessary to make an accurate assessment based on the specific situation of the patient. Objective: To explore the mechanism and rehabilitation methods of lower limb soft tissue sports injury. Methods: In clinical practice, external application of Chinese herbal medicine combined with cold compresses, massage, pot dipping, hot immersion irradiation and other methods were used. Results: The self-made Chinese herbal medicine external ointment, swelling and pain relieving Chinese herbal medicine wine combined with electromagnetic wave therapy instrument is one of the commonly used and effective methods to treat sports injury of lower extremity soft tissue in health care experimental centers. It has the most remarkable effect on local burning, stasis, swelling and pain caused by the soft tissue injury of various lower limbs in various parts of the human body. Conclusions: Timely functional rehabilitation training after sports injury can promote the functional healing and rehabilitation of the body after injury, maintaining the good functional state of each organ system of the body. Level of evidence II; Therapeutic studies - investigation of treatment results.